DEVELOPMENT E-BOOK GUIDED INQUIRY MODEL PHYSICS INTEGRATING MULTIMEDIA FOR WAVE PROPAGATION, STATIONERY AND SOUND WAVE LEARNING MATERIALS - Rathika Maffira; - Yurnetti (Universitas Negeri Padang, 2022)
Covid-19 pandemic has changed learning process commonly done directly in school to distance/ online learning. Consequently, it needs media in order to improve students' motivation and critical thinking skill, such as digital book utilizing interactive multimedia using guided inquiry learning model. Purpose of the research was to measure validity and practicality of guided inquiry model of Physics e-book integrating multimedia for wave propagation, stationary wave, and soundwave learning materials in grade XI of Senior High School. It used a research and development method with Plomp model. The instrument to assess validity was a questionnaire consisted of 4 components, in which each components had 6 aspects of assessment. Meanwhile, the instruments to assess practicality were one-to-one evaluation interview and practicality questionnaire. To analyze data, it used persentase analysis. The Analiysis used is quantitative techniques. Result of validity analysis conducted by 5 validators (3 lecturers from physics department in State University of Padang and 2 physics teachers from SMAN 1 Harau Regency) shows that it is 90,89%, which means very valid. Beside that, result of practicality analysis conducted by 6 students and 2 teachers shows that it is 95% from students and 83,45% from teachers, which means it is very practical. So, it can be concluded that guided inquiry model of Physics e-book integrating multimedia for wave propagation, stationary wave, and soundwave learning materials in grade XI of Senior High School is valid and practical so that it is proper to use in learning process.